UPAYA MENINGKATKAN MINAT BACA DAN KUNJUNG PERPUSTAKAAN OLEH GURU DAN SISWA SMP NEGERI 16 PONTIANAK MELALUI PROGRAM LITERASI - Larasati, Larasati; Hanum, Atiqa Nur Latifa; Madeten, Sisilya Saman (Universitas Tanjungpura, 2023)
Reading and writing skills in Indonesia are still relatively low compared to other countries. Literacy activities can be used as an activity to increase interest in reading and student visits to the library, but it also requires efforts and strategies that must be done. This study aims to determine the strategy used by SMP Negeri 16 Pontianak in increasing interest in reading and visiting through literacy programs. This type of research method is qualitative in the form of descriptive, data collection techniques by interview, indirect observation, and documentation, the research subject is 5 informants. Data analysis with data reduction, data presentation, and conclusion drawing. Validity data tests include trustworthiness, transferability, reliability, and verifiability. Research result 1) reading activities 15 minutes before learning began, and teachers participating in FIM activities, 2) students' interest in visiting the library was still low due to lack of attention to the library, 3) this activity has had a positive impact on students and teachers, it was seen that interest in reading and writing began increases, 4) the existing obstacles are possibility of inadequate facilities and infrastructure to support literacy activities. At the end school's efforts to increase interest in reading and visiting through literacy activities have been going well.